Kripto paralar arasındaki ilişkinin analizi - ERGÜL, NURAY (My University, 2023)
Kripto para piyasası ulaştığı işlem hacmiyle geleneksel para piyasasına rakip duruma gelmiştir. Kripto para piyasasında coinlere alternatif olarak altcoinler piyasaya sunulmuştur. Kripto para piyasasına binlerce coin ve altcoin sunulmasına karşın bitcoinin büyüklüğüne ulaşamamışlardır. Kripto piyasası tezgahüstü bir piyasadır. Bu piyasanın volatilitesi ve riski oldukça yüksektir. Bu piyasanın yüksek getiri imkanı vermesi nedeniyle yatırımcıların ilgi odağı olmaktadır. Çalışmanın amacı kripto para birimlerinin fiyat hareketliliği temel alınarak, bu kripto paralar arasındaki eş-bütünleşme ve nedensellik ilişkileri incelenmektedir. Çalışma kapsamındaki kripto paralar Johansen Eş-bütünleşme Analizi ve Granger Nedensellik Testi kullanılarak incelenmiştir. Johansen eş-bütünleşme test sonucunda iz istatistiği ve max öz değer istatistikleri %5 anlamlılık düzeyindeki kritik değerden yüksek olduğu, H0 hipotezinin reddedildiği ve kripto para serileri arasında eş-bütünleşme ilişkisinin bulunduğunu ortaya koymuştur. Granger Nedensellik Test sonuçları, ADA, BNB, DOGE ve ETH’nin BTC’nin ‘nedeni’ ve BTC’nin ADA, BNB, DOGE ve ETH’nin ‘nedeni’ olduğu ve aralarında çift taraflı bir ilişkisinin bulunduğu belirlenmiştir. ETH ve SOL’un BTC’nin ‘nedeni’ olduğu ve aralarında tek taraflı bir ilişkisinin olduğu görülmüştür. Anahtar Kelimeler: Cryptocurrency, Johansen Cointegration Analysis, Granger Causality Test

The crypto money market has become a rival to the traditional money market with the transaction volume it has reached. Altcoins have been introduced to the market as an alternative to coins in the crypto money market. Although thousands of coins and altcoins were presented to the crypto money market, they could not reach the size of bitcoin. The crypto market is an overthe-counter market. The volatility and risk of this market is quite high. It is the focus of attention of investors because of the high return opportunity of this market. The aim of the study is to examine the cointegration and causality relations between these cryptocurrencies, based on the price mobility of cryptocurrencies. In the study, the independent variable is BTC, and the dependent variables are cryptocurrencies other than BTC. The cryptocurrencies within the scope of the study were examined using Johansen Cointegration Analysis and Granger Causality Test. As a result of the Johansen cointegration test, the trace statistics and the max. eigenvalue statistics were higher than the critical value at the 5% significance level, the H0 hypothesis was rejected and there was a cointegration relationship between the crypto money series.The Granger Causality Test results determined that ADA, BNB, DOGE and ETH are the 'cause' of BTC and BTC is the 'cause' of ADA, BNB, DOGE and ETH, and there is a bilateral relationship between them. It has been seen that ETH and SOL are the 'cause' of BTC and have a onesided relationship between them.
Analysis of the relationship between cryptocurrencies
Keywords: Sosyal ve Beşeri Bilimler; Finans Ekonomisi; Social Sciences and Humanities; Financial Economics; Sosyal Bilimler (SOC); Ekonomi ve İş; EKONOMİ; Social Sciences (SOC); ECONOMICS & BUSINESS; ECONOMICS; Ekonomi ve Ekonometri; Ekonomi, Ekonometri ve Finans (çeşitli); Genel Ekonomi, Ekonometri ve Finans; Sosyal Bilimler ve Beşeri Bilimler; Economics and Econometrics; Economics, Econometrics and Finance (miscellaneous); General Economics, Econometrics and Finance; Social Sciences & Humanities; Cryptocurrency; Johansen Cointegration Analysis; Granger Causality Test